La jurisprudencia sobre los derechos de la naturaleza de la Corte Constitucional del Ecuador (2008-2022): ¿Evolución hacia una teoría sistémica derecho? - Ávila Santamaría, Ramiro Fernando (2023)
The 2008 Constitution of Ecuador, for the first time in global constitutionalism, recognized that nature is a subject and that it has specific rights. The application of these rights has been erratic and jurisprudential development has been slow, due, among other reasons, to the absence of an adequate legal theory. In order to understand the rights of nature, it is necessary to overcome some premises of positive Law. Among them, Law has nothing to do with other disciplines and that nature is an object that can be exploited indiscriminately. Law that recognizes that nature has life, which must be respected and understood from other disciplines, could be called "systemic". With a systemic view, the Constitutional Court of Ecuador has been able to develop the content of the rights of nature. In other cases, the Court has gone through legal paths of private law and also of environmental administrative law. This research shows that the jurisprudence of the Court has had an erratic development and has a systemic jurisprudential line that is expected to be consolidated. In this time of environmental crisis and climate change, recognizing that nature has rights is a way to radically change the dominant legal and political paradigm.